Die Welt als Fiktion: Zur Soziologie des Heftromans - Panke-Kochinke, Birgit (Tectum Verlag, 2023)
Magazine novels serve as a model for a whole range of media products on the entertainment market. Understanding fiction as part of a reality that can be enjoyed without regret is what makes up the entertainment function of this genre. Both the reception and the analysis of magazine novels can lead to the appropriation of fictional world views. But what role do the seemingly antiquated dime novels play in times of media diversi-ty when it comes to gaining insights into the functioning of the world from a sociological perspective? Birgit Panke-Kochinke, historian, sociologist and expert in qualitative methods of social research, outlines the current state of research and develops perspectives for future research.